The Effect of Stress on Visual Function amongst School-Going Children in Mumbai. - Barodawala, Zulfikar S.; Shetty, Aksha; Chande, Prema (Optometry & Visual Performance, 2022)
Background: The prevalence of stress in schoolaged children is reported to be an astonishing 88%. The literature supports an association between functional vision and stress. The objective of this study was to evaluate visual function skills and their association with stress in school-aged children in Mumbai. Methods:A cross-sectional study was conducted on students aged 9 to 15 years in Mumbai. Subjects with no history of ocular disease, surgery, trauma, systemic disease, or ocular or systemic drug use that might induce stress were included. Prediagnosed cases of depression, anxiety, and any systemic or ocular syndrome were excluded from the study. All subjects underwent detailed ocular examination that included slit lamp evaluation, subjective and objective refraction, and undilated retinal evaluation. Subjects were then assessed for colour vision, stereoscopic acuity, contrast sensitivity, and confrontation visual fields, followed by the Stress in Children (SiC) questionnaire. Results: One hundred subjects (mean age 12.3 ± 2.1 years) completed the study; 59% were females. Global mean score (GMS) showed a similar level of stress in females (1.95 GMS) and males (1.94 GMS). Increased stress was correlated with an increase (improvement) in the contrast sensitivity (r = 0.007) and stereo acuity (r = 0.096). GMS scores between astigmatism (2.11 ± 0.37), myopia (1.96 ± 0.24), emmetropia (1.94 ± 0.32), and hyperopia (1.81 ± 0.19) showed no statistical significance (p = 0.549) but were clinically significant. There was no difference found in colour vision and visual field throughout the sample population. Conclusions: Increase in stress was found to be correlated with an improvement in contrast sensitivity and stereo acuity. However, there were no changes found in colour vision and visual fields. Based on refractive error, those with astigmatism showed the highest level of stress, followed by myopia, emmetropia, and hyperopia, respectively.